Cell therapy in patients with heart failure: a comprehensive review and emerging concepts - Bolli, Roberto; Solankhi, Mitesh; Tang, Xiang-Liang; Kahlon, Arunpreet (Cardiovascular research, 2022)
Abstract This review summarizes the results of clinical trials of cell therapy in patients with heart failure (HF). In contrast to acute myocardial infarction (where results have been consistently negative for more than a decade), in the setting of HF the results of Phase I–II trials are encouraging, both in ischaemic and non-ischaemic cardiomyopathy. Several well-designed Phase II studies have met their primary endpoint and demonstrated an efficacy signal, which is remarkable considering that only one dose of cells was used. That an efficacy signal was seen 6–12 months after a single treatment provides a rationale for larger, rigorous trials. Importantly, no safety concerns have emerged. Amongst the various cell types tested, mesenchymal stromal cells derived from bone marrow (BM), umbilical cord, or adipose tissue show the greatest promise. In contrast, embryonic stem cells are not likely to become a clinical therapy. Unfractionated BM cells and cardiosphere-derived cells have been abandoned. The cell products used for HF will most likely be allogeneic. New approaches, such as repeated cell treatment and intravenous delivery, may revolutionize the field. As is the case for most new therapies, the development of cell therapies for HF has been slow, plagued by multifarious problems, and punctuated by many setbacks; at present, the utility of cell therapy in HF remains to be determined. What the field needs is rigorous, well-designed Phase III trials. The most important things to move forward are to keep an open mind, avoid preconceived notions, and let ourselves be guided by the evidence.